Interpretation of the Text and Krishn Chander's Short Story "Chawal Chor" - Suhail, Muhammad Amir; Sahar, Nazia; Awan, Muhammad Saqib Farooq (sourcecoder, 2023)
There have been various trends and ideas in the critique and understanding of literary texts. First, to understand literary text form the authors’ references. Second, to judge art by application of various critical theories. Karishn chandar is an important progressive Urdu short story writer. He is opponent of the feudal, capitalist and colonial system. They are in favor of an equal social and economic system. His short story “CHAWAL CHOR” shows courtly of the former. The story reveals the secret of China’s development in the communist system. The analysis of the story is presented with the intention of author, the text and creative existence of the story and process of reading. This article explore the gaps and spaces how in story. This article offers a new perspective of short story criticism.